(untitled) (Research, Society and Development, 2021)
Deforestation in the Amazon region has been growing a lot in recent decades, including illegally in Conservation Units (CUs). And in order to reduce deforestation, Brazilian legislation allows the creation of a Private Natural Heritage Reserve (RPPN). In light of the above, this study aimed to evaluate the efficiency of RPPNs for the conservation of forest cover in the State of Rondônia, Western Amazon. Nine RPPNs were monitored, with temporal analyzes of land cover using images from the Landsat 5 (TM sensor) and Landsat 8 (OLI sensor) satellites, referring to the years of creation of each RPPN and the current year (2018), and supervised classification (Maximum Likelihood technique). To carry out the classification, 50 to 60 pixels were collected per class of interest (water, exposed soil, forest and urban perimeter) using the Training Sample Manager. Based on the monitoring, it was possible to observe an increase of ≈54% in forest cover in most of the RPPNs in the state, and to detect the efficiency of these areas in the regeneration and preservation of native vegetation. However, the efficiency of RPPNs occurs mainly in rural areas, since urban areas tend to expand, even occupying part of the RPPNs areas, as observed in the municipality of Pimenta Bueno. Therefore, it is concluded that the RPPNs are efficient to control deforestation in rural areas, but more information is needed to assist the planning of strategies aimed at increasing the efficiency of these Conservation Units, especially in areas close to or within urban areas.